Faktor–Faktor Yang Memengaruhi Intensi Berwirausaha Pertanian Siswa Smk Agribisnis Di Kabupaten Cianjur - Burhanuddin; Soedono Sasmoyo Jana Priya, Teuku; Budi Priatna, Wahyu (Forum Agribisnis, 2024)
Cianjur Regency is one of the areas that relies on agriculture as a support for the economy and welfare of its people. In 2020, the number of poor people in the Cianjur Regency decreased, allegedly because of increasing financial prosperity. Simultaneously, the number of entrepreneurs in the Cianjur Regency has increased rapidly. This indicates that entrepreneurship is a contributing factor to the rising financial well-being of the residents in Cianjur Regency. The majority of the productive age group, 15-19 years old, currently studying at vocational high schools, represent crucial capital for advancing agriculture in the Cianjur Regency through entrepreneurship. The aim of this research is to analyze the factors that influence the agricultural entrepreneurship intentions of Agribusiness Vocational School students in the Cianjur Regency. The sample for this study was selected using purposive sampling. The analysis involved descriptive methods and the application of Partial Least Squares Structural Equation Modeling (PLS-SEM). The research results show that the factors that influence the agricultural entrepreneurship intentions of Agribusiness Vocational School students in the Cianjur Regency are attitudes towards behavior (ATB), subjective norms (SNS), and perceived behavioral control (PCB). This research suggests that collaboration between the government, schools, and universities is needed so that vocational school students can maintain and improve the factors that can influence entrepreneurial intentions.